2014
DOI: 10.1128/aem.02146-14
|View full text |Cite
|
Sign up to set email alerts
|

Stratified Microbial Structure and Activity in Sulfide- and Methane-Producing Anaerobic Sewer Biofilms

Abstract: bSimultaneous production of sulfide and methane by anaerobic sewer biofilms has recently been observed, suggesting that sulfate-reducing bacteria (SRB) and methanogenic archaea (MA), microorganisms known to compete for the same substrates, can coexist in this environment. This study investigated the community structures and activities of SRB and MA in anaerobic sewer biofilms (average thickness of 800 m) using a combination of microelectrode measurements, molecular techniques, and mathematical modeling. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 66 publications
1
47
0
2
Order By: Relevance
“…200-500 mg COD/L) for both SRB and MA to co-exist in sewer biofilms, thereby allowing simultaneous methane and sulfide production despite their competition for substrates (Conrad et al, 1987, Raskin et al, 1996, Robinson and Tiedje, 1984. This co-existence is due to stratification of these anaerobic microorganisms in the biofilm (Guisasola et al, 2008, Sun et al, 2014. SRB are found to dominate the microbial community in the top layers of the biofilms where the sulfate concentration is relatively high ( Fig.…”
Section: Methanobaceriales Methanococcales Methanomicrobiales Methmentioning
confidence: 99%
See 4 more Smart Citations
“…200-500 mg COD/L) for both SRB and MA to co-exist in sewer biofilms, thereby allowing simultaneous methane and sulfide production despite their competition for substrates (Conrad et al, 1987, Raskin et al, 1996, Robinson and Tiedje, 1984. This co-existence is due to stratification of these anaerobic microorganisms in the biofilm (Guisasola et al, 2008, Sun et al, 2014. SRB are found to dominate the microbial community in the top layers of the biofilms where the sulfate concentration is relatively high ( Fig.…”
Section: Methanobaceriales Methanococcales Methanomicrobiales Methmentioning
confidence: 99%
“…MA of the Methanosataceae, Methanomicrobiales, Methanosarcinaceae, Methanococcales and Methanocaldococcaceae are detected in rising main sewer biofilms while Methanobacteriales is absent (Mohanakrishnan et al, 2009b). In a recent study of a sewer rising main biofilm it was found that 90% of the MA population belonged to the genus Methanosaeta, and these are obligate acetoclastic methanogens (Sun et al, 2014). MA that use other substrates such as hydrogen only accounted for less than 10% of the total MA population in the sewer biofilm.…”
Section: Methanobaceriales Methanococcales Methanomicrobiales Methmentioning
confidence: 99%
See 3 more Smart Citations